FOSTERING STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT THROUGH GROUP WORK TECHNIQUE - Alek, Alek; Sari, Yulianti (English Department of Faculty of Tarbiyah and Teacher Training, 2016)
Investigation related to reading comprehension has been conducted by a number of researchers and even some of them focussing their research on reading conprehension of narrative text. However, research on this respect needs pay more attention to be scrutinied. The aims of this research are to know and to describe the implementation of group work technique that improve students reading comprehension of narrative text. The problem raised in the research is about low scores of reading comprehension of narrative text gotten by eighth grade students of SMPN 13 Tangerang Selatan. The number of students is 40. Instrument used in this research is observation, questionnaire, and test. The technique is used in collecting data in the research is qualitative data. The qualitative data consisted of observation within the physical activity in the classroom. Moreover, the questionnaire for student is made to support in collecting the data. In analyzing qualitative data, rating scale table is used to measure the observation of students? activities during teaching learning process. Meanwhile, some statistical formula is used in analyzing the numerical data. The findings of this study are: 1. Related to the test result, there are 20% or 8 students passing KKM in pre action test, 47.5% or 21 students passing KKM in cycle 1 test and 80% or 32 students passing KKM in cycle 2. 2. Related to the observation result, the students were more active and interested in learning reading activity in the classroom through group work technique. Furthermore, they could cooperative well with their group. It could be known that the students? reading comprehension in term of narrative text has been improved and teacher was helped in finding the appropriate strategy in teaching reading narrative text